Near‐sighted Justice - BERNHARDT, DAN; NOSAL, ED (Journal of Finance, 2004)
ABSTRACT Chapter 11 structures complex negotiations between creditors and debtors that are overseen by a bankruptcy court. We identify conditions where the court should sometimes err in determining which firms should be liquidated. Such errors affect actions by both good and bad entrepreneurs. We first characterize the optimal error rate without renegotiation. When creditors and debtors can renegotiate to circumvent an error‐riven court, for one class of actions a blind court that ignores all information is optimal. For another class, the court should place the burden of proof on the entrepreneur. The robust feature is that the court should sometimes err.